2019
DOI: 10.1002/path.5186
|View full text |Cite
|
Sign up to set email alerts
|

LGR5 promotes tumorigenicity and invasion of glioblastoma stem‐like cells and is a potential therapeutic target for a subset of glioblastoma patients

Abstract: Glioblastoma (GBM) is the most common and lethal primary malignant brain tumor which lacks efficient treatment and predictive biomarkers. Expression of the epithelial stem cell marker Leucine‐rich repeat‐containing G‐protein coupled receptor 5 (LGR5) has been described in GBM, but its functional role has not been conclusively elucidated. Here, we have investigated the role of LGR5 in a large repository of patient‐derived GBM stem cell (GSC) cultures. The consequences of LGR5 overexpression or depletion have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 43 publications
(110 reference statements)
3
23
0
Order By: Relevance
“…We analyzed the invasion capacity of ESCs in vitro using the collagen invasion assay. Interestingly, we found that all three ESCs were equally or more invasive than U3047MG_SFC (Figure j), that displayed invasive growth in vivo (Figure S1) and previously has been shown to be highly invasive in vitro compared to other SFCs (Xie et al, ). This suggested that the invasive properties of ESCs in vivo might have been hampered by the lack of exogenous factors in the immune‐deficient mouse brain microenvironment.…”
Section: Resultssupporting
confidence: 50%
See 3 more Smart Citations
“…We analyzed the invasion capacity of ESCs in vitro using the collagen invasion assay. Interestingly, we found that all three ESCs were equally or more invasive than U3047MG_SFC (Figure j), that displayed invasive growth in vivo (Figure S1) and previously has been shown to be highly invasive in vitro compared to other SFCs (Xie et al, ). This suggested that the invasive properties of ESCs in vivo might have been hampered by the lack of exogenous factors in the immune‐deficient mouse brain microenvironment.…”
Section: Resultssupporting
confidence: 50%
“…The expression of stem cell markers and extended proliferative capacities of ESCs prompted us to analyze their self‐renewal properties. We used extreme limiting dilution assay (ELDA) and found that the ESCs formed tumorspheres (Figure a–c) in a range previously described for several SFCs (Xie et al, ). In line with their more stem‐like phenotype upon switch to SF media (Figure ), this was also accompanied by a significant increase in self‐renewal (Figure a–c, ESC_to_SFC), where the pGBM cultures (Figure a,b) had similar sphere‐forming capacities as the reference culture U3047MG_SFC (Figure d).…”
Section: Resultsmentioning
confidence: 58%
See 2 more Smart Citations
“…Leucine‐rich repeat‐containing G protein–coupled receptors (LGRs) are a subgroup of the seven‐transmembrane G protein‐coupled superfamily that regulates various physiological processes associated with various diseases, and its member LGR4‐6 has high homology . Many studies have recently explored the biological functions of LGR4‐6 in various human cancer types . LGR4‐6 plays an important role in activating the Wnt/β‐catenin pathway by binding with R‐spondin (RSPO) ligands, which are closely related to tumor progression and invasion …”
Section: Introductionmentioning
confidence: 99%